11- Resolva as expressões:
a)
12 +18 - 13 - 15 + 10 =
b)
16+ [25 - (10 + 12) - 9] =
c)
[(21 + 3 - 2) = 9+5.3] - 6 =
d)
57 + (-35-(-11 + 9 - 4)] =
e)
60 = {2[-7 + 18 = (-3 +12)]} - [7 (-3) -18 = (-2) + 1) =
f)
-8 + {-5+ [(8 - 15) + (10+12)] - 17} =
33 - {2} + (11-15) - [52 + (-3 + 1)] + 8) =
h)
[-12 + (22-5.6)] = (-6+ 2) + 1 =
i) [-(24 - 8). 2-24] + [22 - (-3 + 2)] =
j) {[(8.4+3) = 7+ (3 + 15 + 5) 3] . 2 - (19 - 7) + 632 + 12 =
Soluções para a tarefa
Respondido por
0
Resposta:
a) 12
b) 4
c) 40
d) 28
f) -15
g) -31
i) 375
Perguntas interessantes
Matemática,
7 meses atrás
Geografia,
7 meses atrás
Matemática,
7 meses atrás
Física,
9 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás